Value and indications of laparotomy in Hodgkin's disease with exclusive abdominal presentation - Viola Alles, Alberto; Schroeder, Patricia; Kasdorf, Helmuth (Cirugía del Uruguay, 1979)
Report on 13 cases of Hodgkin's disease with exclusively abdominal topography. There was ganglia involvement in 7 of these patients and abdominal viscera were affected in 6 cases; the former appeared as a prolonged febrile syndrome and the latter as surgical cases. There follows an evaluation of importance of exploratory laparotomy as a means for establishing nosologic diagnosis; this procedure should also involve a complete picture of lesiona! extension of the basic condition